A CLUSTER SOLUTION FOR THE ORGANIZATION OF INDIVIDUAL STUDENT LEARNING IN THE TEACHING OF NATURAL SCIENCES - Atanazar Karimovich Rakhimov; Nadira Abdukhamidovna Mirzayeva; Dilnavoz Bakturdiyevna Saidova (European Science Publishing, 2024)
This article analyzes in detail the individual characteristics and capabilities of students in teaching natural sciences and in the organization of the educational process. A theoretical analysis of the organization of training sessions based on an individual approach in the educational process is presented. According to the principle of the innovative pedagogical cluster, the methodology of the approach to the student's personality is highlighted, based on the effectiveness of its application in practice.
Keywords: pedagogical educational cluster, individual approach, individual training